Konsep al-Ḍarūrah Tentang Vaksin Astrazeneca Perspektif Majelis Ulama Indonesia - Jamaluddin Jamaluddin; Kasjim Salenda; Abdul Wahid Haddade (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2022)
This study aims to comprehensively describe the general overview of al-ḍarūrah and the AstraZeneca vaccine, examine the analysis of fiqh principles regarding al-ḍarūrah in the use of the AstraZeneca vaccine by the MUI, and analyze the MUI fatwa Number 14 of 2021 concerning the Law on the Use of the Covid-19 Vaccine Product. AstraZeneca. This study uses a qualitative-descriptive research method with library research techniques. The results showed that al-ḍarūrah is a condition that threatens human life or part of its body. Al-ḍarūrah referred to in the use of the AstraZeneca vaccine is that there is an urgent need condition (al-ḥājah al-syar'iyyah) that occupies the condition of al-ḍarūrah. This is in line with the fiqh rule "al-ḥājah al-'āmmah wa al-khāssah tanzīlu manzilah al-ḍarūrah" namely general and special needs occupy the position of al-ḍarūrah. The MUI fatwa regarding the use of AstraZeneca's Covid-19 vaccine on the grounds of urgent need that occupies the position of al-ḍarūrah, can be categorized as al-ḍarūrah for treatment, where the Covid-19 vaccine of AstraZeneca product is in accordance with awābiṭ al-ḍarūrah, namely: first, al-arrah arūrah really happens instantly, not waiting for a deliberate al-ḍarūrah; second, there is no other solution except to violate the prohibition; and third, based on reliable expert testimony that there are no drugs other than those that are forbidden.